EVALUASI PENGATURAN DALAM PEMUNGUTAN RETRIBUSI DAERAH DI KABUPATEN LAMPUNG TENGAH - Sudarti Sudarti (Fiat Justisia: Jurnal Ilmu Hukum, 2016)
In conducting regional autonomy, the regional government needs funding, and one of the funding sources is regional retribution. Middle Lampung had provisioned 3 Regional Regulations which regulated retributions of common service, business service, and particular permit. Implementations of these three regional regulations could not yet be applied fully. The arrangement of retributions of telecommunication tower control, animal slaughter house, and advertising business permit had their own orientations. The regulation of retribution collection of telecommunication tower control was no longer in accordance with Decision of Constitutional Court number 46/PUU-XII/2014 on May 26th, 2015. The Regent Regulation about the conduct of retribution collection from animal slaughter house had not been yet provisioned, there was no qualified animal slaughter house and human resource. Regent Regulation about advertising business retribution collection had not been yet provisioned and there was no data of advertising business available as basics for collecting retribution. Keywords: Evaluation, Regulation, Retributions